AB0016 COMBINED GENOME-WIDE ASSOCIATION AND GENE-EXPRESSION META-ANALYSIS IDENTIFIES NOVEL PSORIASIS GENES. (June 2019) - Saeed, Mohammad
Abstract : Background: Psoriasis (Ps) is a common, inflammatory disorder affecting skin, joints and associated connective tissue, with significant genetic underpinnings. Multiple genome-wide association studies (GWAS) have been conducted with identification of several Ps loci. However, these only explain about a third of Ps genetic risk indicating that additional loci of modest effect remain to be discovered (1). Objectives: Identify novel psoriasis genes that have functional consequences for psoriasis by altered gene-expression Methods: Association clustering methods such as gene- and locus-based tests are more powerful than single variant analysis for identifying modest genetic effects (2, 3). Here, a dbGAP GWAS dataset (4) for Ps (pha002855: 1348 Ps cases and 1368 controls, genotyped for 448K SNPs) was analyzed using the locus-based algorithm, OASIS (3), to identify 13 highly significant loci other than the HLA-C locus. In these loci 50 genes were identified using SNIPPER, which were then subjected to gene expression analysis in three Ps GEO datasets. Results: This genetic and functional analysis identified a total of 18 genes that were significantly associated and had altered expression in psoriasis skin. The most significant of these were two genes that were two-fold upregulated in Ps, IL12B ( P = 9x10 -11 ) and TTC39B ( P = 3x10 -12 ) and two genes that were repressed <50%, MAML2 ( P = 8x10 -19 ) and EBF1 ( P = 1x10 -12 ). Interestingly, the expression of IL23R remained unaltered. Other genes that were significantly upregulated (1.5 – 2.0 fold) were IL12RB2, TTC1 and PSMD6 . Genes that were also significantly repressed (0.5 - 0.8 fold) were SERBP1, ATXN7, PSIP1, ZNF385D, SIPA1L1 . Conclusion: This combined genetic and functional meta-analysis elucidated novel genes, functional networks and pathways for psoriasis. These results will lead to important insights into the immunopathogenesis and treatment of psoriasis. References: [1] Tsoi LC, Stuart PE, Tian C, et al. Large scale meta-analysis characterizes genetic architecture for common psoriasis associated variants. Nat Commun. 2017May24;8:15382. PMID: 28537254. [2] Luo L, Peng G, Zhu Y, et al. Genome-wide gene and pathway analysis. Eur J Hum Genet. 2010Sep;18(9):1045-53. PMID: 20442747. [3] Saeed M. Novel linkage disequilibrium clustering algorithm identifies new lupus genes on meta-analysis of GWAS datasets. Immunogenetics. 2017May;69(5):295-302. PMID: 28246883. [4] Nair RP, Duffin KC, Helms C, et al. Genome-wide scan reveals association of psoriasis with IL-23 and NF-kappaB pathways. Nat Genet. 2009Feb;41(2):199-204. PMID: 19169254. Disclosure of Interests: Mohammad Saeed Shareholder of: Partner at ImmunoCure - laboratory, which performs Autoimmune antibody testing, Grant/research support from: Participation in EULAR 2019 Meeting is sponsored by High-Q Pharma Pak